Mechanical and thermal properties, and comparative life-cycle impacts, of stabilised earth building products. (20th May 2020) - Narayanaswamy, Abhilash Holur; Walker, Peter; Venkatarama Reddy, B.V.; Heath, Andrew; Maskell, Daniel
Highlights: Use of cement, alkali-activation and waste materials to produce stabilised compressed earth. Detailed experimental results for mechanical and thermal properties presented. Environmental impacts of novel materials are compared in a Life Cycle Assessment. Abstract: The study presented here investigates the use of alkali-activation and waste materials in stabilised compressed earth construction products. Experimental results for mechanical and thermal properties are presented. Environmental impacts are also compared in a Life Cycle Assessment together with a wider discussion of construction practicalities. Construction and demolition waste shows potential as an aggregate, with processed ground blast furnace slag, together with fly ash, particularly promising for alkali-activated stabilisation. Thermal conductivities of materials using the processed ground blast furnace slag were noticeably lower. Alkali-activated compressed earth blocks appear most promising for reducing the global warming potential of stabilised earth construction.